Robot Programming at Different Abstraction Levels - Fernandes, Carla; Barros, Renata; Albuquerque, Erika; Sá, Sarah; Gonçalves, Luiz (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
The teaching of programming is an important issue related to Educational Robotics whereas in many cases students have different levels of knowledge in programming. Since several robots have a specific programming language, some students are excluded from the class due to their poor knowledge in the area. This paper presents the possibility of abstraction in the programming complexity by making use of the web environment multi-platform W-Educ. The presented approach allows different groups of users to perform the same activity making use of different resources.